Sleep alterations following COVID-19 are associated with both neuroinflammation and psychological disorders, although at different times - Pellitteri, Gaia; Surcinelli, Andrea; De Martino, Maria; Fabris, Martina; Janes, Francesco; Bax, Francesco; Marini, Alessandro; Milanic, Romina; Piani, Antonella; Isola, Miriam; Gigli, Gian Luigi; Valente, Mariarosaria (Frontiers in Neurology, 2022)
Introduction: Since the end of 2019, SARS-CoV-2 rapidly spread all over the world impacting on mental health and sleep habits. Insomnia, impaired sleep quality, and circadian rhythm alterations were all observed during the pandemic, especially among healthcare workers and in acute and post-acute COVID-19 patients. Sleep disruption may induce a pro-inflammatory state associated with an impairment of immune system function. Objective: We investigated the relationship between sleep alterations, psychological disorders and inflammatory blood biomarkers in post-acute COVID-19 patients. Methods: We enrolled 47 subjects diagnosed with COVID-19 pneumonia at Santa Maria della Misericordia University Hospital (Udine, Italy) between March and May 2020. Selected patients were evaluated at two months (T1) and 10 months (T2) after discharge. Each time, we collected clinical interviews, neurological examinations and self-administered questionnaires to assess sleep and life quality, anxiety, depression, and post-traumatic stress disorder. Blood biomarkers of endothelial activation, neuroinflammation, and inflammatory cytokines were also measured at each follow-up. Collected variables were analyzed using comparisons between groups and linear regression models. Results: Prevalence of insomnia increased from 10.6% up to 27.3% (p=0.02) after COVID-19. A poor sleep quality was found in 41.5% of patients at both study visits. At T1 follow-up, poor sleepers showed higher levels of neurofilament light chain (p<0.001), vascular cell adhesion molecule 1 (p=0.034), and interleukin 10 (p=0.031); no significant associations were found between sleep quality and psychological disorders. At T2 follow-up, a lower sleep quality was associated with higher levels of vascular cell adhesion molecule 1 (p=0.044) and interleukin 8 (p=0.034), but also with higher scores for anxiety (p<0.001), depression (p=0.009) and post-traumatic stress disorder (p=0.007). Conclusion: Our results suggest an association of poor sleep quality with both psychological disorders and neuroinflammation, although at different times, in previously hospitalized patients with moderate-to-severe COVID-19.